2011
DOI: 10.1136/tc.2010.042192
|View full text |Cite
|
Sign up to set email alerts
|

Carcinogenic tobacco-specificN-nitrosamines in US cigarettes: three decades of remarkable neglect by the tobacco industry

Abstract: Modification of tobacco curing methods and other changes in cigarette manufacturing techniques could substantially reduce the levels of tobacco-specific nitrosamines (TSNA), a group of potent carcinogens, in cigarette smoke. In 1999, two major U.S. cigarette manufacturers stated their intent to move towards using tobaccos low in TSNA. Since there is no information available on current TSNA levels in tobacco of various cigarettes available in the U.S., we examined the levels of these carcinogens in currently ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
73
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(79 citation statements)
references
References 21 publications
5
73
1
Order By: Relevance
“…We identified 14 published studies that met the data inclusion criteria (Adams et al, 1987;Brunnemann and Hoffmann, 1991;Brunnemann et al, 1996;Counts et al, 2005Counts et al, , 2006Djordjevic et al, 1991;Hecht et al, 1979;Hoffmann et al, 1979Hoffmann et al, , 1982Patskan et al, 2008;Roemer et al, 2004;Stepanov et al, 2012;Swauger et al, 2002). Table 1 presents cigarette product identifications, levels of MS smoke tar (mg/cigarette), NNK (ng/cigarette), and NNN (ng/cigarette), and sources of the data presented in this review.…”
Section: Tsna Levels In Ms Smoke: 35 Years Of Datamentioning
confidence: 96%
See 1 more Smart Citation
“…We identified 14 published studies that met the data inclusion criteria (Adams et al, 1987;Brunnemann and Hoffmann, 1991;Brunnemann et al, 1996;Counts et al, 2005Counts et al, , 2006Djordjevic et al, 1991;Hecht et al, 1979;Hoffmann et al, 1979Hoffmann et al, , 1982Patskan et al, 2008;Roemer et al, 2004;Stepanov et al, 2012;Swauger et al, 2002). Table 1 presents cigarette product identifications, levels of MS smoke tar (mg/cigarette), NNK (ng/cigarette), and NNN (ng/cigarette), and sources of the data presented in this review.…”
Section: Tsna Levels In Ms Smoke: 35 Years Of Datamentioning
confidence: 96%
“…Concerns have been raised by the tobacco control community suggesting that little progress has been made by the tobacco industry to reduce TSNA levels in cigarette smoke (Stepanov et al, 2012). It has also been suggested that TSNA levels in cigarette smoke may have even increased over time (Burns et al, 2011a).…”
Section: Introductionmentioning
confidence: 99%
“…Cotinine, NNAL, and NNN in toenails were first reported by the research group of Stepanov et al [50,51,57]. NNAL and NNN, tobaccospecific N-nitrosamines, are of particular concern due to their carcinogenic potency [58]. Nicotine, cotinine, NNAL, and NNN in toenails were validated as biomarkers of tobacco smoke exposure by investigation of their correlation with other biomarkers for smoking such as plasma nicotine, cotinine and trans-3 0 -hydroxycotinine, and urinary NNAL [51].…”
Section: Caffeine Nicotine and Cotininementioning
confidence: 95%
“…Such a high lung cancer risk is due to the physical-chemical characteristics of the mainstream cigarette smoke (MSS). In fact, the cigarette-generated particles contain more than 3500 semi-volatile and non-volatile compounds, some of them classified as carcinogenic such as hydrocarbons (PAHs; [24][25][26][27]), dioxins and furans [28], heavy metals [25,[29][30][31][32][33][34], and tobacco-specific nitrosamines [25,31,[35][36][37]. Moreover, in fresh unaged tobacco cigarette mainstream smoke particle concentrations of about 4 × 10 9 part cm −3 were measured, with an arithmetic mean diameter of about 0.2 µm [38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, cigarette mainstream smoke (MSS) is the smoke emerging from the mouth end of a cigarette during puffing [36]. Mainstream smoke consists of an aerosol containing liquid droplets (particulate phase) suspended in the gas vapor phase, which is generated by overlapping burning, pyrolysis, pyrosynthesis, distillation, sublimation, and condensation processes [37].…”
Section: Introductionmentioning
confidence: 99%